Centroamérica: geopolítica, militarización y crisis humanitaria (Otros Temas) - Benítez Manaut, Raúl (2015)
The article contains an analysis of the principal factors that cause insecurity within the countries of Central America, and its geopolitical and humanitarian effects, principally to Mexico and the US. This phenomenon adds a though challenge to the governments, due to the resources that have criminal organizations. Therefore, public insecurity and drug trafficking turn into the principal security issues to the government and to the citizens. For ends and purposes, within this article, the region of Central America has been divided into two: Northern Triangle (Guatemala, Honduras, El Salvador), and Southern Triangle (Nicaragua, Costa Rica, Panama).